BISMUTH MINERALS OF SULFIDE-MAGNETITE ORES FROM THE AKTASH DEPOSIT (WESTERN KARAMAZAR, TAJIKISTAN) - U.A. Yatimov; N.R. Ayupova; I.A. Blinov; V.A. Kotlyarov (Минералогия)
Bismuth mineralization is studied in sulfide-magnetite ores of the Aktash deposit in Western Karamazar (Northern Tajikistan), which is hosted in the Middle–Upper Paleozoic sedimentary and intrusive rocks. The higher Bi contents are related to the presence of its numerous minerals including native bismuth, bismuthine, Cu–Ag–Pb–Bi sulfosalts (wittichenite, emplectite, aikinit, friedrichite and salzburgite) and Bi oxides (bismite, zavarazkite) in assemblage with galena, chalcopyrite, garnet, pyroxene, epidote and anglesite. The Ag-bearing varieties of wittichenite (Cu,Ag)3 BiS3 , aikinite (Pb,Ag)CuBiS3 and galenobismuthite (Pb,Ag)Bi2 S4 are identified. Most of the bismuth minerals were first described not only for this deposit, but for the ore region as well. The mode of occurrence of Bi can be used to refine the genetic features of the deposit.